Pengaruh Myofascial Release Dan Ultrasound Terhadap Penurunan Nyeri Myofascial Syndrome Upper Trapezius Pada Pasien Rumah Sakit Semen Gresik - Moh Adi Bayu Arifin; Yohanes Deo Fau; Fransisca Xaveria Hargiani; Sartoyo Sartoyo (Jurnal Keperawatan Muhammadiyah, 2023)
Objective: This study was conducted to analyze whether myofascial release therapy and ultrasound intervention had an effect on reducing the intensity of upper trapezius pain with upper trapezius myofascial syndrome in patients at Semen Gresik Hospital. Methods: This article uses pre and post test experiments conducted on 20 patients with myofascial syndrome upper trapezius pain at Semen Gresik Hospital. The sampling technique used was purposive sampling, with the sampling technique according to predetermined inclusion and exclusion criteria. Results: Myofascial release exercise therapy and ultrasound intervention had a significant effect on reducing myofascial pain syndrome upper trapezius in 20 patients at Rs. Semen Gresik as the respondent. Significant results between myofascial release exercise therapy and ultrasound intervention on myofascial pain syndrome upper trapezius were shown from asymp. sig. 2-tailed in the Wilxocon signed rank test is 0.000 <0.05. Conclusion: Myofascial release therapy and ultrasound given to patients had a significant effect on reducing myofascial pain syndrome upper trapezius in 20 patients at Rs. Semen Gresik with significant results asymp. sig. 2-tailed in the Wilxocon signed rank test is 0.000 <0.05.